Advancing scholarship: HSJ attains scopus indexing - embarking on a new scientific journey - Fajar, Jonny Karunia (Heart Science Journal, 2024)
Following the inclusion of Heart Science Journal (HSJ) in the Scopus index, we present this announcement outlining our forward trajectory and strategies aimed at elevating the quality of HSJ. Since the outset of 2024, HSJ has been formally indexed in Scopus, marking a significant milestone in our journey. We extend profound appreciation to our authors, editorial team, and reviewers for their diligent efforts and steadfast dedication, pivotal in realizing this accomplishment. In our ongoing pursuit of enhancing journal quality, we extend a global invitation to authors to contribute their research endeavors to HSJ. In essence, HSJ embarks on a new chapter within Scopus, and we extend a cordial invitation to scientists worldwide to partake in this collaborative endeavor.